1986
DOI: 10.1111/j.1365-2125.1986.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of doxazosin in elderly normotensives.

Abstract: The pharmacokinetics of doxazosin were studied in 12 normotensive elderly volunteers aged 62-89 years. There was marked inter-individual variability in all the parameters derived but the disposition of doxazosin was similar in both sexes. These results were compared to those of a group of young normotensive volunteers aged 23-39 years studied previously under comparable conditions. The volume of distribution increased significantly with age although the bioavailability and clearance were not significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This is a reflection of the observation that its pharmacokinetic characteristics are also similar in older and younger volunteers (29,30).…”
Section: Discussionmentioning
confidence: 86%
“…This is a reflection of the observation that its pharmacokinetic characteristics are also similar in older and younger volunteers (29,30).…”
Section: Discussionmentioning
confidence: 86%
“…Any postural effects can usually be avoided by careful dose titration from an initial 1 mg dose of doxazosin. With respect to the half life of doxazosin, this has been found to be similar in older and younger hypertensive patients 24 and volunteers. 12 …”
Section: Discussionmentioning
confidence: 63%
“…The use of doxazosin in older patients is supported by the similarities in the elimination half-life of doxazosin in older and younger volunteers [19]. Furthermore, it has been demonstrated that bioavailability is not influenced by age.…”
Section: Pharmacokinetic Parameters Of Doxazosinmentioning
confidence: 70%